Fluconazole non-susceptible breakthrough candidemia after prolonged low-dose prophylaxis: a prospective FUNGINOS study. Issue 5 (May 2018) - Orasch, Christina; Mertz, Dominik; Garbino, Jorge; van Delden, Christian; Emonet, Stephane; Schrenzel, Jacques; Zimmerli, Stefan; Damonti, Lauro; Mühlethaler, Konrad; Imhof, Alexander; Ruef, Christian; Fehr, Jan; et al.
Highlights: FUNGINOS conducted a nationwide prospective study of candidemia in Switzerland. Breakthrough candidemia (BTC) occurred in 8% of 567 consecutive candidemias. BTC was observed in hemato-oncological patients with gastrointestinal mucositis. Prolonged low-dose fluconazole prophylaxis was associated with non-susceptible BTC. Severity of infection and mortality were not increased in BTC compared to non-BTC. Abstract: Objectives: Breakthrough candidemia (BTC) on fluconazole was associated with non-susceptible Candida spp. and increased mortality. This nationwide FUNGINOS study analyzed clinical and mycological BTC characteristics. Methods: A 3-year prospective study was conducted in 567 consecutive candidemias. Species identification and antifungal susceptibility testing (CLSI) were performed in the FUNGINOS reference laboratory. Data were analyzed according to STROBE criteria. Results: 43/576 (8%) BTC occurred: 37/43 (86%) on fluconazole (28 prophylaxis, median 200 mg/day). 21% BTC vs. 23% non-BTC presented severe sepsis/septic shock. Overall mortality was 34% vs. 32%. BTC was associated with gastrointestinal mucositis (multivariate OR 5.25, 95%CI 2.23–12.40, p < 0.001) and graft-versus-host-disease (6.25, 1.00–38.87, p = 0.05), immunosuppression (2.42, 1.03–5.68, p = 0.043), and parenteral nutrition (2.87, 1.44–5.71, p = 0.003). Non- albicans Candida were isolated in 58% BTC vs. 35% non-BTC (p = 0.005). 63% of 16 BTC occurring after 10-day fluconazole were non-susceptible ( Candida glabrata, Candida krusei, Candida norvegensis ) vs. 19% of 21 BTC ( C. glabrata ) following shorter exposure (7.10, 1.60–31.30, p = 0.007). Median fluconazole MIC was 4 mg/l vs. 0.25 mg/l (p < 0.001). Ten-day fluconazole exposure predicted non-susceptible BTC with 73% accuracy. Conclusions: Outcomes of BTC and non-BTC were similar. Fluconazole non-susceptible BTC occurred in three out of four cases after prolonged low-dose prophylaxis. This implies reassessment of prophylaxis duration and rapid de-escalation of empirical therapy in BTC after short fluconazole exposure.